Rasionalisme Hegel: Metode Dialektis dalam Mendekati Masalah Metafisika - Theguh Saumantri (Undiksha, 2023)
Metaphysics is an essential thing in the study of philosophy. Metaphysics is a part of human knowledge related to the question of the most profound nature of existence. One of the philosophers who compiled a metaphysical system was G.W.F Hegel, who stated that the basic meaning of reality is human. The focus of the discussion in this research was to describe the basis for the productivity of Hegel’s thinking, especially rationalism (dialectics), and its relevance to theological issues in the religious realm. This research was library research with a philosophical approach that aimed to search and examine data or information about the characters’ thoughts. The research results found that Hegel’s dialectic through the mechanism of the thesis, antithesis, and synthesis has been used to approach metaphysical problems. Therefore, the most crucial thing can be applied in religious life with the spirit of critical dialogue toward a healthy and constructive religious association.